Our friend Sam - Mayer, Mercer, 1943- (Mayer, Mercer, 1943- Little Critter book., 2002)
Little Critter and Gabby find a caterpillar in the yard, and they take care of it until it turns into a beautiful butterfly and flies away. Includes word recognition lists.